Vacuums of the sea: Ecological function of large coral reef benthic scavengers in suppressing crown-of-thorns starfish (COTS) outbreaks - Mohsen Kayal; Hunter Lenihan (Ideas in Ecology and Evolution, 2025)
Despite their drastic impacts on coral reefs, outbreaks of the coral-feeding seastar crown-of-thorns starfish (COTS), Acanthaster, have remained a scientific enigma. Significant efforts in coral reef conservation science have been dedicated to identifying natural predators able to exert demographic control on COTS and prevent population outbreaks. These efforts are motivated by empirical evidence showing that reefs within marine protected areas are less prone to COTS outbreaks than reefs open to fishing where potential COTS predators have been reduced or removed functionally from food webs. Research findings point towards COTS’ early life-stages as a major demographic bottleneck for COTS populations, with various reef fish and benthic organisms identified as preying upon the seastar. Yet, no species or species groups have been clearly identified as exerting enough top-down control to influence COTS population increases or prevent outbreaks. We report the benthic scavenging behavior of eagle rays (family Myliobatidae), a large-bodied predator, feeding in coral rubble fields of Kanaky New Caledonia, critical habitats where juvenile COTS find refuge and food and accumulate to produce population outbreaks. We argue that with their effective substrate-sucking feeding behavior, similar to vacuums of the sea, eagle rays may be a hitherto unidentified predator able to exert significant control on COTS populations. Eagle rays and other large benthic scavengers were previously neglected in the search for major COTS predators. Relatively little existing data show that eagle ray populations in Kanaky New Caledonia’s lagoon are more abundant inside than outside marine protected areas, which concords with the hypothesis that they could be responsible for the mitigation of COTS outbreaks as reported within reserves. We advocate for further investigations on the role of eagle rays and other large benthic scavengers in controlling COTS outbreaks, and the importance of preserving the unique ecological function of sea vacuums for coral reef conservation.